Penilaian Kurikulum Sains Program Ijazah Sarjana Muda Perguruan dalam aspek konteks, input, proses dan produk - Yahya, Fauziah (2016)
This study aims to identify the implementation practices of Science lecturers in imparting Program Ijazah Sarjana Muda Perguruan (PISMP) Science Curriculum at Teacher Education Institute (IPG) Malaysia in the context, input, process and product dimensions besides seeking the influence among each dimension. This study employs a mixed method design which combine the quantitative-qualitative mixed method approaches. Samples of the study consist of 105 Science lecturers who are currently serving and offering Science specialization at 20 IPGs all over Malaysia. Quantitative data were collected through a set of questionnaires and an interview method was employed for qualitative data gathering. Cronbach’s alpha value for the questionnaire was 0.97. Statistical Package for the Social Science (SPSS) and AMOS were used in analysing the quantitative data and the qualitative data were analysed using manual procedure. Results of the study indicate that the mean for the level of implementation of Science Curriculum by IPG Science lecturers was at a high level which was 4.66. The results also show that there is no significant difference in the context, input, process and product dimensions in the implementation practices of Science Curriculum by Science lecturers when imparting PISMP Science Curriculum at IPG all over Malaysia based on gender, teaching experience in school and teaching experience at IPG. Subsequently based on Structural Equation Modelling (SEM), it was found that the context dimension shows an influence on the product dimension. Two elements in the context dimension which are the aim of the curriculum and the curriculum objective also showed significant contributions towards the product dimension. Input dimension represented by lesson content element, pedagogical skills, evaluation and assessment, and selection and usage of teaching and learning resources also show significant contributions on the product dimension. The process dimension which is represented by implementation of teaching and learning element based on lesson content, implementation of pedagogical skills, implementation of evaluation and assessment, and also implementation of selection and usage of teaching and learning resources also influenced the product dimension. In conclusion, the study shows that the integrated influence of context, input, and process dimensions towards product dimension in the implementation practices of Science lecturers in imparting PISMP Science Curriculum is preferrably better than practising and implementing it loosely and separately. The study also indicates that in each dimension there is a significant element which contributes to the maximum implemention of the PISMP Science Curriculum. This study has also established a Profile of The Implementation of the PISMP Science Curriculum by Science lecturers at IPG. Further research should be carried out by intergrating the profile established with the Science lecturers teaching methods in order to improve and enhance the effectiveness of the implementation of the PISMP Science Curriculum at IPG in the future.